Katarzyna Wądolny-Tatar’s Proposal to Read Books about Children - Szczukowski, Ireneusz (Porównania, 2023)
The purpose of the review is to discuss the monograph by Katarzyna Wądolny Tatar Reconstructive Narrations, Intervention Narrations, Literary Representations of Childhood, Warsaw 2021